2001
DOI: 10.1097/00007890-200110150-00024
|View full text |Cite
|
Sign up to set email alerts
|

Early Peri-Operative Glycaemic Control and Allograft Rejection in Patients With Diabetes Mellitus: A Pilot Study

Abstract: This pilot study suggests that hyperglycemia may be associated with an increased risk of both allograft rejection and postoperative infection in patients with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(52 citation statements)
references
References 7 publications
0
49
0
3
Order By: Relevance
“…Most studies have reported that transplant patients with hyperglycemia and PTDM after transplantation have higher rates of rejection, infection, and rehospitalization (100,102,107).…”
Section: Posttransplantation Diabetes Mellitusmentioning
confidence: 99%
“…Most studies have reported that transplant patients with hyperglycemia and PTDM after transplantation have higher rates of rejection, infection, and rehospitalization (100,102,107).…”
Section: Posttransplantation Diabetes Mellitusmentioning
confidence: 99%
“…Thomas et al [27] [30], изучая функцию почечного аллотрансплантата (ПАТ), выяснили, что сни-жение его функции в двух группах достоверно не различалось; однако 5-летняя выживаемость трансплантата у пациентов с ПТСД составила 70% по сравнению с 90% у больных без СД. Также выявлено, что инфекции были главным осложне-нием в группе с ПТСД и составили 53% по сравне-нию с 16% в контрольной группе.…”
Section: Review Articles and Lecturesunclassified
“…Bei Nierentransplantation war das Risiko einer Abstoßung fast verdoppelt, wenn bei Aufnahme nach der Operation die Glukosewerte über 110 mg/dl erhöht waren [14]. Das Phäno-men war ähnlich ausgeprägt bei Diabetikern [15].…”
Section: Prognostische Bedeutung Der Hyperglykämieunclassified